Tinjauan Sistematis: Komplikasi dan Kekambuhan pada Perbaikan Hernia Inguinalis Laparoskopik VS Terbuka - Yohanes Windu Tiar Prakosa; Radian Adhiputra Antonius (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Inguinal hernia represents the most common surgical condition with lifetime prevalence of 27% in men and 3% in women, requiring optimal definitive surgical intervention. To analyze and compare complications and recurrence rates between laparoscopic and open inguinal hernia repair based on current literature. Systematic review following PRISMA 2020 guidelines with literature search on PubMed, Scopus, Web of Science, and Cochrane Library from 2019-2025. Ten studies involving 95,192 patients were analyzed including randomized controlled trials, cohort studies, and national database analyses. Laparoscopic technique demonstrated lower acute postoperative pain, faster recovery, and shorter hospital stay. However, inguinodynia was reported higher in laparoscopic (9.4-14.1%) compared to open (1.5%) in several early studies. Long-term recurrence rates in adult population showed comparable results between both techniques when performed by experienced surgeons, while in pediatric bilateral cases there was tendency of higher recurrence in laparoscopic (3.7% vs 2.0% at 3 years). Technique selection should be individualized considering patient characteristics, hernia type, surgeon experience, and patient preference. Laparoscopic technique is optimal for bilateral hernias and patients requiring rapid recovery, while open remains safe choice in populations with severe comorbidities.